Gender and age differences in cardiovascular reflexes in response to upright tilting - AL-Shamma, Yesar MH.; Al-Abidy, Sameer M.K. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: the integrity of cardiovascular reflexes & autonomic activities can be assessed by different tests and different techniques. However most of these studies carried out on male subject & usually on young group only .very little researches available concerning the differences in cardiovascular reflexes between male & female in different age group.Aim of study: is to investigate the differences in cardiovascular reflexes in young , old male & female in response to go head up tilting using totally non- invasive system .Sub. & Methods: this study was carried out in AL-Najaf teaching hospital on 85 normal sub. , 41 males c6 44 females they were divided into two age groups (20-40 years) & (41-60 years) for both sex. The blood pressure was measured by sphygmomanometer (BP) cardiac out put (Co) measured by Echocardiography technique, heart rate by ECG & the peripheral vascular resistance was measured by dividing the (BP) over (Co) according to Ohm’s law . All these measurements were first made in supine position at a study state & then all the measurements were repeated on 60 ’ head up tilting.Results: the results indicate that there was a significant difference between the two sexes in both age groups by using this totally non - invasive system to measure all the above mention homodynamic variables.Conclusion: this study provided great advantages for the investigation of abnormal cardiovascular reflexes in patients with orthostatic postural hypotension on the detection of some autonomic dysfunction or in case of prolonged bed rest after post operative surgery.